2022
DOI: 10.3390/molecules27134188
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Lipids from Arecaceae Palm Fruits in Brazil

Abstract: Arecaceae palm tree fruits (APTFs) with pulp or kernel rich in oil are widely distributed in six Brazilian biomes. APTFs represent a great potential for the sustainable exploitation of products with high added value, but few literature studies have reported their properties and industrial applications. The lack of information leads to underutilization, low consumption, commercialization, and processing of these fruit species. This review presents and discusses the occurrence of 13 APTFs and the composition, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 202 publications
(435 reference statements)
0
15
0
Order By: Relevance
“…vulgare fruit is eaten raw, prepared into juices, and used as an indispensable ingredient of the very popular French Guianan dish "bouillon d'awara" that is traditionally eaten during Easter. Cold-pressing of the mesocarp gives tucuma oil, and cold-pressing of the hard, white endosperm from the rigid, black seed gives tucuma butter that has an unusually high concentration of the fatty acid lauric acid in addition to myristic acid and oleic acid [79,80]. Both tucuma oil and tucuma butter are edible and suitable for cooking and also for preparing nourishing and moisturizing beauty products, anti-aging creams, soaps, body lotions, and products for damaged hair [80,81].…”
Section: Antioxidant Vitamins: Vitamin A: Astrocaryum Vulgare Mart (A...mentioning
confidence: 99%
“…vulgare fruit is eaten raw, prepared into juices, and used as an indispensable ingredient of the very popular French Guianan dish "bouillon d'awara" that is traditionally eaten during Easter. Cold-pressing of the mesocarp gives tucuma oil, and cold-pressing of the hard, white endosperm from the rigid, black seed gives tucuma butter that has an unusually high concentration of the fatty acid lauric acid in addition to myristic acid and oleic acid [79,80]. Both tucuma oil and tucuma butter are edible and suitable for cooking and also for preparing nourishing and moisturizing beauty products, anti-aging creams, soaps, body lotions, and products for damaged hair [80,81].…”
Section: Antioxidant Vitamins: Vitamin A: Astrocaryum Vulgare Mart (A...mentioning
confidence: 99%
“…It has been reported that the fruit patawa has potential for the production of edible oil suitable as an ingredient in cosmetics, soaps, and foods such as popsicles, ice cream, and concentrated juices [ 74 , 98 ]. Its oil still has antimicrobial activity and high oxidative stability compared to other commercial oils [ 4 , 7 ]. Despite its interesting nutritional composition, patawa is still relatively unknown in Brazil, and it is used only by the local population in the regions where it is grown [ 101 ].…”
Section: Macro and Micronutrientsmentioning
confidence: 99%
“…Geonoma , Syagrus , Bactris , Atallea , Allagoptera , Astrocaryum , and Euterpe are the genera with the highest number of occurrences worldwide [ 3 ]. Recently, the lipid composition [ 4 ], nutraceutical potential [ 5 ], and the chemical properties [ 6 ] of different species of fruits from the Arecaceae family have been reported. Bacaba ( Oenocarpus bacaba ), patawa ( Oenocarpus bataua ), juçara ( Euterpe edulis ), açaí ( Euterpe oleracea ), buriti ( Mauritia flexuosa ), buritirana ( Mauritiella armata (Mart.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, macauba palms can be cultivated in areas where oil palms cannot be produced, resulting in lower risks of a tropical rain forest clearance [ 4 ]. Macauba palms also have a high socioeconomic importance due to their wide occurrence [ 5 ]. As such, the macauba palm has recently aroused the interest of scientists and agronomists as a new sustainable source of vegetable oil with significant potential for use in the cosmetic, food, and energy industries [ 1 , 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macauba palms also have a high socioeconomic importance due to their wide occurrence [ 5 ]. As such, the macauba palm has recently aroused the interest of scientists and agronomists as a new sustainable source of vegetable oil with significant potential for use in the cosmetic, food, and energy industries [ 1 , 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%